2021
DOI: 10.1051/0004-6361/202140564
|View full text |Cite
|
Sign up to set email alerts
|

The GOGREEN survey: Internal dynamics of clusters of galaxies at redshift 0.9–1.4

Abstract: Context. The study of galaxy cluster mass profiles (M(r)) provides constraints on the nature of dark matter and on physical processes affecting the mass distribution. The study of galaxy cluster velocity anisotropy profiles (β(r)) informs the orbits of galaxies in clusters, which are related to their evolution. The combination of mass profiles and velocity anisotropy profiles allows us to determine the pseudo phase-space density profiles (Q(r)); numerical simulations predict that these profiles follow a simple… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 187 publications
(296 reference statements)
1
12
0
Order By: Relevance
“…5, top-left panel). Our results support the findings of several studies based on both DM-only and hydrodynamical simulations (Taylor & Navarro 2001;Rasia et al 2004;Dehnen & McLaughlin 2005;Ludlow et al 2010;Navarro et al 2010), and of previous observational studies (Biviano et al 2013;Munari et al 2014;Biviano et al 2016Biviano et al , 2021, and do not support claims against the power-law behavior of Q(r) (Nadler et al 2017). Since our results are based on a stack cluster, we can neither confirm nor reject the numerical result of Schmidt et al (2008) against the universality of Q(r) across different cosmological halos.…”
Section: Discussion Of Results On Sigv Stacked Clusterssupporting
confidence: 66%
See 2 more Smart Citations
“…5, top-left panel). Our results support the findings of several studies based on both DM-only and hydrodynamical simulations (Taylor & Navarro 2001;Rasia et al 2004;Dehnen & McLaughlin 2005;Ludlow et al 2010;Navarro et al 2010), and of previous observational studies (Biviano et al 2013;Munari et al 2014;Biviano et al 2016Biviano et al , 2021, and do not support claims against the power-law behavior of Q(r) (Nadler et al 2017). Since our results are based on a stack cluster, we can neither confirm nor reject the numerical result of Schmidt et al (2008) against the universality of Q(r) across different cosmological halos.…”
Section: Discussion Of Results On Sigv Stacked Clusterssupporting
confidence: 66%
“…Chae (2014) found that Q(r) is a power law for Coma cluster elliptical galaxies with a slope of 1.93 ± 0.06. On larger scales, Q(r) has been measured in several clusters of galaxies over the redshift range 0.06-1.34, and it has always been found to be similar to, or at least consistent with, the simulation-based expectations, both when Q(r) was defined using the total mass density profile ρ(r) (Biviano et al 2013;Munari, Biviano, & Mamon 2014;Biviano et al 2016Biviano et al , 2021 and when the tracer ν(r) was used instead for tracers of different colors and luminosities (Munari, Biviano, & Mamon 2015;Aguerri et al 2017;Capasso et al 2019).…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…The remaining three clusters were drawn from the South Pole Telescope (SPT) survey (Brodwin et al 2010;Foley et al 2011;Stalder et al 2013) and were initially detected via their Sunyaev-Zeldovich (Sunyaev & Zeldovich 1970) signature and later spectroscopically confirmed. In Table 2.1, we provide properties of our cluster sample including halo mass (M200) and radial scale (R200) -which are both obtained using the MAMPOSSt method (Mamon et al 2013) as outlined in Biviano et al (2021) -along with redshift and the number of spectroscopic cluster members with M > 10 10 M .…”
Section: Gogreen and Gclass Cluster Samplementioning
confidence: 99%
“…Properties of our GOGREEN cluster sample, including M 200 , R 200 , cluster redshift, and the number of spectroscopic members (with M > 10 10 M ). The values in the R 200 and M 200 columns were obtained using the MAMPOSSt method(Mamon et al 2013) as outlined inBiviano et al (2021). Details regarding the cluster membership criteria are discussed in Sec.…”
mentioning
confidence: 99%